Memorandum on the Beveridge Report - Beveridge, William Henry Beveridge, Baron, 1879-1963 (London : Communist Party of Great Britain)
1943-02 1943 1940s 28 pages Average working-class earnings in 1938 were around £3 5s. per week. With war-time increases in wage rates but without war-time overtime, they would average about £4 2s. per week at the present time. The single man on our scales when unemployed would draw a subsistence allowance of three-eighths of average weekly earnings; the married man without dependent children, about five-eighths; and the married man with one child, less than three-quarters. The subsistence scale is therefore to be regarded as a protection from sheer physical want. It cannot be regarded as giving a reasonable standard of life or as a basis for fixing wages. COST OF LIVING We note that the Beveridge scales assume a cost of living scale 25 per cent. above pre-war. At the present moment it is 30 per cent. above pre-war, and were it not for Government subsidies to certain essential foodstuffs it would be probably in the region of 40 per cent. above pre-war. We are therefore of the opinion that arrangements should be made in the Act or Acts of Parliament in which the Social Security Plan is embodied, for paying higher rates of benefit on the basis of higher contributions from workers, employers and State, should the cost of living in 1943 be higher than that assumed in the Report. OLD AGE PENSIONERS One of the greatest objections to the Beveridge proposals is that they do not improve in any marked degree the condition of the old age pensioner who is on existing supplementary pensions. The present scale for a single pensioner (without resources) is 19/- plus 2/6 war bonus, plus 2/6 winter relief — i.e., 24/- per week in winter time. In addition, he can, under certain conditions, get a grant for clothing. If his rent is higher than 5/- per week, he can get a grant. 13 15X/2/103/272